"A step toward smart city and green transportation: Eco-friendly waste PET management to enhance adhesion properties of asphalt mixture". (18th October 2021) - Haider, Safeer; Hafeez, Imran
Highlights: Suitable compatibility of waste PET modified asphalt binder with different aggregate minerals was determined in laboratory. Silica aggregate quarries have relatively weaker bond with waste PET in comparison with others aggregate minerals (dolomite, calcium carbonate and dolerite). All results showed that, it will be a sustainable use of waste PET in flexible pavements, the savings from highway projects will uplift the other human life standards in natural disaster like COVID-19 specially in under-developed countries. Abstract: The failure of the flexible pavements causes human casualties as well as economic loss due to interruption of communication systems. Especially in underdeveloped countries, these types of failure in communication systems take relatively longer time to recover. As a result, there is a huge loss in economy of the country. Fatigue, rutting, and moisture susceptibility are the main contributors towards the failure of the flexible pavements. To avoid this, waste polyethylene terephthalate (PET) modified asphalt binder and aggregates containing different minerals composition have been utilized in this experimental work to make strong bond between asphalt binder and aggregate interface against water interaction. Tests on both loose and dense specimens were conducted in the laboratory to assess resistance against water interaction of asphalt mixture. All the laboratory test data showed that aggregate quarries containing higher amount of silica have poor bonding properties than aggregates containing (lesser silica minerals). This study recommends the use of waste PET with basic nature (relatively more hydrophobic) aggregate to make more smart asphalt pavements. Moreover, being an economical use of waste PET in flexible pavements, the savings from highway projects will uplift the other human life standards in natural disaster like COVID-19 specially in under-developed countries.